Ventricular tachycardia characteristics and outcomes with catheter ablation vs. antiarrhythmic therapy: insights from the VANISH trial. Issue 7 (14th January 2022) - Deyell, Marc W; Doucette, Steve; Parkash, Ratika; Nault, Isabelle; Gula, Lorne; Gray, Christopher; Gardner, Martin; Sterns, Laurence D; Healey, Jeff S; Essebag, Vidal; Sapp, John L
Abstract: Aims: Catheter ablation is superior to escalated antiarrhythmic drugs among patients with ventricular tachycardia (VT) and prior myocardial infarction (MI). However, it is uncertain whether clinical VT characteristics, should influence choice of therapy. The purpose of this study was to evaluate whether presentation with electrical storm and the clinical VT cycle length predicted response to ablation vs. escalated antiarrhythmic therapy. Methods and results: All patients enrolled in the Ventricular Tachycardia Ablation vs. Escalated Antiarrhythmic Drug Therapy in Ischaemic Heart Disease (VANISH) trial were included. The association between VT cycle length and presentation with electrical storm and the primary outcome of death, subsequent VT storm or appropriate ICD shock was evaluated. Among the study population of 259 patients, escalated antiarrhythmic drug therapy had worse outcomes for those presenting with a VT cycle length >400 ms [<150 b.p.m., 89/259, hazard ratio (HR) 1.7 (1.02–3.13)]. This effect was more pronounced among those taking amiodarone at baseline [HR of 2.22 (1.19–4.16)]. Presentation with VT storm (32/259) did not affect the primary outcome between groups. However, those presenting with VT storm on amiodarone had a trend towards worse outcomes with escalated antiarrhythmic therapy [HR 4.31 (0.55–33.93)]. Conclusion: The VT cycle length can influence response to either ablation or escalated drug therapy in patients with VT and prior MI. Those with slow VT had improved outcomes with ablation. Patients presenting with electrical storm demonstrated similar outcomes to the overall trial population, with a trend to benefit of catheter ablation, particularly in those on amiodarone.